Persepsi dan faktor penentu pemilihan produk pastry dan bakery sehat pada generasi Z: Studi kasus kuantitatif di Indonesia - Luthfi, Tristy Firlyanie; Novianti, Selvi; Sanggramasari, Sandra; Duhita, Narendra; Septian, Abil Refi; Eleanora, Charissa; Alistiawati, Amelia (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: The trend of healthy eating continues to grow in Indonesia, particularly among Gen-Z, including pastry and bakery products. According to the Badan Pusat Statistik, the consumption of pastry and bakery products in Indonesia increased by 2,62% in 2023. However, the understanding of healthy products, such as pastry and bakery items, remains limited. This study aims to explore the perceptions and factors influencing the selection of these products among Gen-Z.Objective: To understand the perceptions and reasons behind Gen-Z’s selection of healthy pastry and bakery products in Indonesia, as there is a concern that commercially available products may not meet health standards if consumed excessively.Method: This study employs a quantitative approach, collecting data from 203 Gen-Z respondents across Indonesia. The measurement of perceptions regarding healthy products was conducted using a 10-question questionnaire, analyzed through frequency distribution. The reasons for product selection were measured using 23 questions based on the Food Choice Questionnaire, utilizing a Likert scale and factor analysis, following validity and reliability tests using SPSS.Results: 51,72% of respondents have a "moderate" understanding of healthy products. The main selection factors—Health, Weight Control, and Sensory Appeal—account for 65,131% of the Total Variance Explained. For Gen-Z in Indonesia, the most preferred products are gluten-free, low-sugar, high-fiber, low-calorie, low-carb, low-fat, and great-tasting.Conclusion: A new factor has emerged as a reason for selecting pastry and bakery products, which is a combination of Health, Weight Control, and Sensory Appeal, shaping Gen-Z’s perception of healthy pastry and bakery products in Indonesia.